2023
DOI: 10.1038/s41597-023-02034-0
|View full text |Cite
|
Sign up to set email alerts
|

Agrimonia: a dataset on livestock, meteorology and air quality in the Lombardy region, Italy

Abstract: The air in the Lombardy region, Italy, is one of the most polluted in Europe because of limited air circulation and high emission levels. There is a large scientific consensus that the agricultural sector has a significant impact on air quality. To support studies quantifying the role of the agricultural and livestock sectors on the Lombardy air quality, this paper presents a harmonised dataset containing daily values of air quality, weather, emissions, livestock, and land and soil use in the years 2016–2021, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Anyway, it can be assumed that the values obtained do not differ from the levels generally observed in urban areas, both residential and industrial sites. Numerous studies have reported exposure to air pollutants and often refer to single cities, short time periods, and speci c air pollutants (Fassò et al 2023;Gilardi et al 2023). In particular, the phenomena of air pollution from benzene-based molecules (benzene is a ubiquitous pollutant of indoor and outdoor air, as well as class 1 carcinogenic substance, according to IARC -International Agency for Research on Cancer) have been extensively described in the recent literature, referring to various regions of Italy (Martellini et Ciacci et al 2023).…”
Section: Voc Pro Lesmentioning
confidence: 99%
“…Anyway, it can be assumed that the values obtained do not differ from the levels generally observed in urban areas, both residential and industrial sites. Numerous studies have reported exposure to air pollutants and often refer to single cities, short time periods, and speci c air pollutants (Fassò et al 2023;Gilardi et al 2023). In particular, the phenomena of air pollution from benzene-based molecules (benzene is a ubiquitous pollutant of indoor and outdoor air, as well as class 1 carcinogenic substance, according to IARC -International Agency for Research on Cancer) have been extensively described in the recent literature, referring to various regions of Italy (Martellini et Ciacci et al 2023).…”
Section: Voc Pro Lesmentioning
confidence: 99%
“…The overall dataset examined in the present study was characterized, with respect to previous experiences of data collection for Agrimonia [43], for the use of the bottom-up LPi, together with the hourly data on ammonia concentrations and the main meteorological parameters, in long-term time series.…”
Section: Annual Emission Estimatesmentioning
confidence: 99%
“…The overall dataset examined in the present study is characterized, with respect to previous experiences of data collection Agrimonia [37], for the use of the bottom up LPi, together with the hourly data of ammonia concentrations and the main meteorological parameters on long-term time series.…”
Section: Meteorological Parameters Measurements Sitesmentioning
confidence: 99%